Photo-Fenton approach for the determination of organic nitrogen in rainwater - Crispim, Cristina P.; Nogueira, Raquel F.P. [UNESP]; Ometto, Jean P.; Campos, M. Lucia A.M. (Elsevier, 2018)
The importance of taking the organic forms of nitrogen (ON) into account when estimating atmospheric nitrogen deposition has been known for a long time. However, there is still only a modest amount of data on organic nitrogen in rainwater worldwide, largely due to the difficulties and uncertainties imposed by the available analytical methods. This work offers a simple, low cost, and reliable method for the determination of ON in rainwater, based on the photo-Fenton process under UV irradiation. The recovery of ON was determined using individual solutions of urea, serine, glycine, and histidine, as well as a mixture of all these compounds plus arginine. Close to 100% organic nitrogen recoveries were obtained for solutions containing 50 μmol N L−1, using addition of 50 μmol L−1 Fe2+ and 2.0 mmol L−1 H2O2, with adjustment of the pH to ∼2.5 and irradiation for 90 min. The average reagent blank was <2.0 μmol N L−1. The homemade reactor employed a 400 W high pressure mercury lamp, from which the external bulb had been manually removed. The reactor ventilation was controlled in order to maintain the temperature at ∼85 °C. The precision of the method ranged from 1.3 to 5.7%, based on ON recovery. Rainwater collected on an event basis in Ribeirão Preto (São Paulo State, Brazil) presented ON concentrations from 4.1 to 34.3 μmol L−1 (n = 18), corresponding to 13–45% of the total nitrogen, with an average contribution of 33%. Precision of ≤7.0% was obtained for the analysis of ON in rainwater.
Keywords: Advanced oxidation processes; Dissolved organic nitrogen; Nitrogen biogeochemical cycle; TiO2